COVID-19 and hyperglycaemic emergencies: perspectives from a developing country. Issue 1 (2nd January 2022) - Bhikoo, Raisa; Conradie-Smit, Marli; Van Wyk, Gerhard; Lahri, Sa'ad; Du Plessis, Elizabeth; Cilliers, Jaco; Hugo, Susan; Coetzee, Ankia
Abstract : Background: Pre-existing diabetes mellitus (DM), hyperglycaemia and obesity emerged as prognostic factors in severe Coronavirus disease 2019 (COVID-19). To date, no published South African studies report on the incidence, presentation and outcomes of DM and diabetic ketoacidosis (DKA) during the COVID-19 pandemic. Objective: To reflect on the diagnosis, management, obstacles to care and outcome of four patients who were admitted to Tygerberg Hospital, Cape Town, South Africa. The outcome of these cases that presented consecutively with DKA and COVID-19 between May and July 2020 are discussed, the presentation, management and long-term considerations with specific reference to DKA and COVID-19 are reviewed. Results: Three of the four patients had newly diagnosed DM. These patients presented with non-specific symptoms and signs leading to a diagnosis of both DKA and COVID-19. The single surviving patient in this series was known to have pre-existing DM but discontinued his insulin upon becoming unwell. One patient required insulin therapy at the time of initial presentation a week or two prior to the current admission but received metformin instead. She was diagnosed with COVID-19 after having poor glycaemic control for over one week, after which insulin was initiated. Ultimately she died as a result of severe hypokalaemia. One patient primarily had respiratory complaints, severe COVID-19 pneumonia and received concomitant dexamethasone. Glycaemic control in this patient was complicated by both hypo- and hyperglycaemia. Conclusion: These cases highlight the management challenges faced by many developing countries, and identify the missed opportunities in persons presenting with COVID-19 and hyperglycaemic emergencies.